Travel Tales in the Promised Land (Palestine) - May, Karl, 1842-1912; Schoonover, James D. (Salt Lake City, UT : Project Gutenberg, 2008)
"Travel Tales in the Promised Land (Palestine)" by Karl May is a narrative travelogue written in the early 20th century. The text recounts the adventures and encounters of the protagonist, who journeys through Palestine, focusing particularly on his relationships with local residents, including the merchant Mustafa Bustani and his son Thar. The narrative likely explores themes of friendship, cultural exchange, and the layers of inter-religious dynamics in a historical context. At the start of the book, the reader is introduced to the protagonist, who has a close friendship with the merchant Mustafa Bustani. The opening scene highlights the bond between them as they discuss personal matters and their families, shedding light on the cultural complexities of life in the Promised Land. Mustafa's son, Thar, is depicted as a lively and imaginative child, often engaging in fanciful play and heroics. This introduction sets the stage for an exploration of the rich tapestry of life in Palestine, characterized by humor, gravity, and the deep interpersonal connections that transcend religious and cultural boundaries. (This is an automatically generated summary.)
Release date is 2008-06-08
Keywords: Middle East -- Description and travel